Functional Redundancy in HIV-1 Viral Particle Assembly - O'Carroll, Ina P. (American Society for Microbiology, 2012)
Expression of a retroviral Gag protein in mammalian cells leads to the assembly of virus particles. In vitro, recombinant Gag proteins are soluble but assemble into virus-like particles (VLPs) upon addition of nucleic acid. We have proposed that Gag undergoes a conformational change when it is at a high local concentration and that this change is an essential prerequisite for particle assembly; perhaps one way that this condition can be fulfilled is by the cooperative binding of Gag molecules to nucleic acid. We have now characterized the assembly in human cells of HIV-1 Gag molecules with a variety of defects, including (i) inability to bind to the plasma membrane, (ii) near-total inability of their capsid domains to engage in dimeric interaction, and (iii) drastically compromised ability to bind RNA. We find that Gag molecules with any one of these defects still retain some ability to assemble into roughly spherical objects with roughly correct radius of curvature. However, combination of any two of the defects completely destroys this capability. The results suggest that these three functions are somewhat redundant with respect to their contribution to particle assembly. We suggest that they are alternative mechanisms for the initial concentration of Gag molecules; under our experimental conditions, any two of the three is sufficient to lead to some semblance of correct assembly.